Nyadran: Local Wisdom in Response to Gardner’s Theory in Early Childhood Education - Fatia Rosyida; Joko Pamungkas; Muthmainah (Universitas Pendidikan Ganesha, 2025)
The quality of early childhood education continues to face challenges in providing learning methods that optimally accommodate the diverse potentials of children. One potential alternative is to utilize local wisdom as a contextual approach to support the development of children's multiple intelligences. This study aims to analyze the potential of the Nyadran tradition as an educational medium in stimulating various intelligences in early childhood, based on Gardner’s theory of multiple intelligences. Employing a descriptive qualitative approach, this research involved 42 early childhood students and 4 teachers from two early childhood education institutions. Data were collected through participatory observation, semi-structured interviews, and documentation, then analyzed using Miles & Huberman’s interactive analysis model. The findings indicate that the Nyadran tradition facilitates activities that integrally develop visual-spatial, interpersonal, intrapersonal, naturalistic, musical, and bodily-kinesthetic intelligences. Activities within this tradition encourage children to actively engage, collaborate, express themselves, explore the environment, and reflect on themselves through various cultural practices. This study concludes that Nyadran has the potential to serve as an effective local wisdom-based pedagogical strategy to support the holistic development of early childhood learners. The implications encourage educators to integrate local cultural values into meaningful and relevant learning experiences for children.